The Effect of Conditional Cash Transfers on Educational Opportunities - Experimental Evidence from Latin America - Andrés Ham (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2010)
Conditional Cash Transfers (CCTs) provide income to the poor in an effort to improve current welfare and promote investment in human and social capital to prevent future deprivation. So far, the impact evaluation literature has focused on estimating current effects on outcomes such as school attendance, consumption and labor supply. However, these studies overlook potential redistributive effects, mainly via the equalization of opportunities. The ensuing analysis draws from recent contributions in the literature on opportunities and incorporates these with impact evaluation methods. The main findings indicate a remarkable redistributive effect of CCTs and a positive initial impact on opportunities. However, while mean outcomes improve markedly, the evidence suggests that the distribution of opportunities readjusts to the positive gains, perhaps indicating deeply rooted inequities. These results are expected to encourage discussion on program impact beyond those evaluated and addressing the programs' long-term consequences.
Keywords: D30; D63; I38; J22; 330; poverty; opportunities; education; children; impact evaluation; conditional cash transfers; Transfereinkommen; Bildungsinvestition; Bildungsverhalten; Lateinamerika